The advantage of positive text-background polarity is due to high display luminance. - Buchner A; Mayr S; Brandt M (Ergonomics, 2009)
Reading text from computer screens is better when text is printed in dark letters on light background (positive polarity) than when it is printed in light letters on dark background (negative polarity). An experiment is presented that tests whether this positive polarity advantage is due to the fact that overall display luminance is typically higher for positive than for negative polarity displays. To this end, text-background polarity and display luminance were manipulated independently. No positive polarity advantage was observed when overall display luminance of positive and negative polarity displays was equivalent. There was only an effect of display luminance, with better performance for the higher-luminance displays. This suggests that the positive polarity advantage is in fact due to the typically higher luminance of positive polarity displays. Readability of text presented on computer screens (e.g. on websites) is better when the overall display luminance level is high, as in positive polarity displays (dark letters on light background). Display polarity per se does not affect readability.